Phytoplankton communities from San Francisco Bay Delta respond differently to oxidized and reduced nitrogen substrates—even under conditions that would otherwise suggest nitrogen sufficiency - Glibert, Patricia M.; Wilkerson, Frances P.; Dugdale, Richard C.; Parker, Alexander E.; Alexander, Jeffrey; Blaser, Sarah; Murasko, Susan (Frontiers in Marine Science, 2014)
The effect of equivalent additions of nitrogen (N, 30-40 μM-N) in different forms (ammonium, NH4+, and nitrate, NO3-) under conditions of different light exposure on phytoplankton community composition was studied in a series of four, 5-day enclosure experiments on water collected from the nutrient-rich San Francisco Bay Delta over two years. Overall, proportionately more chlorophyll a and fucoxanthin (generally indicative of diatoms) was produced per unit N taken up in enclosures enriched with NO3- and incubated at reduced (~15% of ambient) light intensity than in treatments with NO3- with high (~60% of ambient) light exposure or with NH4+ under either light condition. In contrast, proportionately more chlorophyll b (generally indicative of chlorophytes) and zeaxanthin (generally indicative of cyanobacteria) was produced in enclosures enriched with NH4+ and incubated under high light intensity than in treatments with low light or with added NO3- at either light level. Rates of maximal velocities (Vmax) of uptake of N substrates, measured using 15N tracer techniques, in all enclosures enriched with NO3- were higher than those enriched with NH4+. Directionality of trends in enclosures were similar to phytoplankton community shifts observed in transects of the Sacramento River to Suisun Bay, a region in which large changes in total N quantity and form occur. These data substantiate the growing body of experimental evidence that dichotomous microbial communities develop when enriched with the same absolute concentration of oxidized vs. reduced N forms, even when sufficient N nutrient was available to the community prior to the N inoculations.